New taxa and a combination in Glomerales (Glomeromycota, Glomeromycetes) - Janusz Błaszkowski; Szymon Zubek; Paweł Milczarski; Ryszard Malinowski; Piotr Niezgoda; Bruno Tomio Goto (MycoKeys)
This article presents the results of morphological studies, as well as comparisons and phylogenetic analyzes of sequences of four arbuscular mycorrhizal fungi (AMF, phylum Glomeromycota): Dominikia indica, Dominikia indica strain 211, Isolate 517, and Isolate 524. Dominikia indica strain 211 was previously characterized only by sequences of the 45S nuc rDNA region (= 18S, partial, ITS-1-5.8S-ITS2, 28S, partial) and the rpb1 gene (without any morphological data) that were deposited in GenBank under the incorrect name “Dominikia indica strain 211”. Its 45S sequences differed from the original D. indica sequences and, consequently, resulted in erroneous phylogenetic classification of this species. Isolate 517 and Isolate 524 slightly differed in morphology from Macrodominikia compressa (formerly D. compressa) and Microkamienskia perpusilla (formerly Kamienskia perpusilla), respectively. Microkamienskia perpusilla was originally found in a maritime dune site of Italy in 2009 and not yet reported from any other habitat in the world. Our sequence comparisons and analyses showed that D. indica represents a new genus, here created under the name Delicatispora gen. nov. with De. indica comb. nov., and Dominikia indica strain 211 is a new species, described as Dominikia paraminuta sp. nov. These analyses also indicated that Isolate 517 is conspecific to M. compressa and confirmed the correctness of the transfer of D. compressa by other AMF researchers to Macrodominikia gen. nov. with M. compressa comb. nov. Morphological studies of our M. compressa specimens grown in culture showed that the original description of this species is incomplete and, therefore, the description was emended. Phylogenetic analyses of Isolate 524 proved its conspecificity to Mk. perpusilla and thus revealed its second site of occurrence, i.e., the coastal dunes of the Hel Peninsula in northern Poland.